ANALYSIS OF THE INFLUENCE OF ROA, DER, PER, COMPOSITE STOCK PRICE INDEX AND COMPANY SIZE AGAINST INITIAL RETURN - Andini Nurwulandari (Sean Institute, 2022)
The study aims to analyze the Influence of Roa, Der, Per, Combined Stock Price Index and Company Size to find out how initial returns developed in 46 companies listed on the Capital Market in 2016-2021. The analysis method used is secondary data that is data obtained indirectly by researchers. The data source used in the research comes from the Indonesian Capital Market Electronic Library in the Capital Market. The results of this study explain that the absence of significant differences in stock returns in the period before and after the stock split can be interpreted that the stock split event does not bring information / signaling about future profits.